1996
DOI: 10.1227/00006123-199604000-00053
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Peridural Scar and Recurrent Radicular Pain After Lumbar Discectomy: Magnetic Resonance Evaluation

Abstract: The purpose of this study was to investigate the presence of any correlation between recurrent radicular pain during the first six months following first surgery for herniated lumbar intervertebral disc and the amount of lumbar peridural fibrosis as defined by MR imaging. 197 patients who underwent first-time single-level unilateral discectomy for lumbar disc herniation were evaluated in a randomized, double-blind, controlled multicenter clinical trial. Clinical assessments, performed by physicians blinded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
3
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(175 citation statements)
references
References 33 publications
6
148
3
18
Order By: Relevance
“…These factors include misdiagnosis, technical failure, new disc protrusion, bony compression, excessive fibrosis, facet syndrome, infection and instability 7,[22][23][24] . In a retrospective study Osterman et al 25 found a risk of 25,1% of further spinal surgery in the first ten years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include misdiagnosis, technical failure, new disc protrusion, bony compression, excessive fibrosis, facet syndrome, infection and instability 7,[22][23][24] . In a retrospective study Osterman et al 25 found a risk of 25,1% of further spinal surgery in the first ten years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can cause symptomatic problems, such as radicular pain. Ross et al (1996) show a close relationship between epidural adhesions and recurrent radicular pain or lower back pain after a successful lumbar discectomy. In addition, epidural adhesion leads to difficulties during a revision surgery.…”
Section: Introductionmentioning
confidence: 87%
“…A variety of biological, pharmacological and synthetic materials have been tested in vitro or used in vivo as space-occupying agents. Free or pedicle fat graft (Barberá et al, 1978), Silastic (Alkalay et al, 2003), methylene blue (Farrokhi et al, 2011), ADCON-L (Einhaus et al, 1997), Vicryl mesh (Nussbaum et al, 1990), methacrylate (Lawson et al, 1991), carboxymethyl cellulose (Rodgers et al, 2003), polyethylene oxide (Rodgers et al, 2003), haemostatic agents (Doğulu et al, 2009;Songer et al, 1995), mitomycin C (Lee et al, 2004;Lee et al, 2006), pimecrolimus , absorbable cement (Mehdi et al, 2014), topical high-molecularweight hyaluronan (Kato et al, 2005;Massie et al, 2005;Songer et al, 1990;Chen et al, 2014;Semra et al, 2015) and anti-inflammatory medications (Ross et al, 1996;Cekinmez et al, 2010) have been used with inconsistent results. Therefore, development of a new anti-adhesive material to prevent epidural fibrosis shall benefit spine laminectomy surgery.…”
Section: Mh Hu Et Almentioning
confidence: 99%
“…In this condition scar tissue adheres to the dura mater or nerve roots are formed in order to repair the local defect of the vertebral lamina created by the laminectomy. However, this scar formation may be compressive and restrict the mobility of the nerve root which often leads to an unfavourable clinical outcome (North et al 1991;Songer et al 1995;Ross et al 1996). Concurrently epidural fibrosis increases the hazards of revision spine surgery and contributes to the occurrence of the "failed back surgery syndrome" (Robertson 1996;Ross et al 1996;Chan and Peng 2011).…”
Section: Discussionmentioning
confidence: 99%